Morphologic Features of Gastric-type Cervical Adenocarcinoma in Small Surgical and Cytology Specimens. (May 2019) - Turashvili, Gulisa; Morency, Elizabeth G.; Kracun, Mihaela; DeLair, Deborah F.; Chiang, Sarah; Soslow, Robert A.; Park, Kay J.; Murali, Rajmohan
Abstract : Gastric-type cervical adenocarcinoma (GCA) is a human papillomavirus-unassociated, aggressive, chemorefractory tumor. Well-differentiated examples may exhibit bland morphologic appearances, which could potentially lead to misdiagnosis, particularly in limited material. We sought to characterize the morphologic features of GCA in surgical biopsy and cytology specimens. We identified patients with histologic diagnoses of GCA or minimal-deviation adenocarcinoma between 2004 and 2017. Available slides from biopsy, curettage, and cytology specimens were reviewed. Fifty-nine specimens (37 histology, 22 cytology) were reviewed from 23 patients, including histology specimens alone from 6 patients, cytology specimens alone from 4 patients, and both types of specimen from 13 patients. The median patient age was 52 yr (range, 29–83 yr). Biopsies showed well-to-moderately differentiated adenocarcinomas composed of cells with pale or foamy cytoplasm and well-defined cytoplasmic borders. Nuclei exhibited mild-to-moderate pleomorphism with small nucleoli. The diagnosis was challenging in a minority of biopsies in which neoplastic glandular epithelium was scant, fragmented, and/or well differentiated. Cytology slides showed single and crowded clusters of tumor cells with pale, foamy, and/or vacuolated cytoplasm and well-defined cytoplasmic borders. Nuclei were moderately pleomorphic, round to oval with one or more nucleoli. Of 20 submitted biopsies, GCA was suspected by the submitting pathologist in only 5 (25%) cases. Awareness of the morphologic features and use of confirmatory ancillary studies (eg, immunohistochemistry for markers of gastric differentiation and human papillomavirus testing) will allow accurate diagnosis of these aggressive tumors in biopsy and cytology specimens.